STAT‐3 contributes to pulmonary fibrosis through epithelial injury and fibroblast‐myofibroblast differentiation. Issue 1 (31st August 2015) - Pedroza, Mesias; Le, Thuy T.; Lewis, Katherine; Karmouty‐Quintana, Harry; To, Sarah; George, Anuh T.; Blackburn, Michael R.; Tweardy, David J.; Agarwal, Sandeep K.
ABSTRACT: Lung fibrosis is the hallmark of the interstitial lung diseases. Alveolar epithelial cell (AEC) injury is akey step that contributes to a profibrotic microenvironment. Fibroblasts and myofibroblasts subsequently accumulate and deposit excessive extracellular matrix. In addition to TGF‐β, the IL‐6 family of cytokines, which signal through STAT‐3, may also contribute to lung fibrosis. In the current manuscript, the extent to which STAT‐3 inhibition decreases lung fibrosis is investigated. Phosphorylated STAT‐3 was elevated in lung biopsies from patients with idiopathic pulmonary fibrosis and bleomycin (BLM)‐induced fibrotic murine lungs. C‐188‐9, a small molecule STAT‐3 inhibitor, decreased pulmonary fibrosis in the intraperitoneal BLM model as assessed by arterial oxygen saturation (control, 84.4 ± 1.3%; C‐188‐9, 94.4 ± 0.8%), histology (Ashcroft score: untreated, 5.4 ± 0.25; C‐188‐9, 3.3 ± 0.14), and attenuated fibrotic markers such as diminished α‐smooth muscle actin, reduced collagen deposition. In addition, C‐188‐9 decreased the expression of epithelial injury markers, including hypoxia‐inducible factor‐1α (HIF‐1α) and plasminogen activator inhibitor‐1 (PAI‐1). In vitro studies show that inhibition of STAT‐3 decreased IL‐6‐ and TGF‐β‐induced expression of multiple genes, including HIF‐1α and PAI‐1, in AECs. Furthermore, C‐188‐9 decreased fibroblast‐to‐myofibroblast differentiation. Finally, TGF‐β stimulation of lung fibroblasts resulted in SMAD2/SMAD3‐dependent phosphorylation of STAT‐3. These findings demonstrate that STAT‐3 contributes to the development of lung fibrosis and suggest that STAT‐3 may be a therapeutic target in pulmonary fibrosis.—Pedroza, M., Le, T. T., Lewis, K., Karmouty‐Quintana, H., To, S., George, A. T., Blackburn, M. R., Tweardy, D. J., Agarwal, S. K. STAT‐3 contributes to pulmonary fibrosis through epithelial injury and fibroblast‐myofibroblast differentiation. FASEB J. 30, 129‐140 (2016). www.fasebj.org